Unified Numerical FFR with Adaptive Bandwidth for 5G and Beyond Multilayer Multisector Networks - Muhammad Yaser; Iskandar; M. Sigit Arifianto; Khoirul Anwar (Ital Publication, 2026)
The present research introduces a unified numerical formulation for Fractional Frequency Reuse (FFR) and a user composition-based adaptive bandwidth allocation strategy for multi-layer/multi-sector cell architectures. The proposed FFR metric explicitly accumulates sub-band usage across the inner–outer and inter-sector layers, thereby normalizing diverse reuse patterns into a single, consistent number. This formulation remains consistent with the classical definition (reducing to 1/N reuse under certain conditions), approaches full reuse when multi-layer/sector coordination is applied, and provides a simple yet powerful link between reuse configurations and capacity predictions in 5G and beyond networks. Comprehensive simulations based on a realistic urban macrocell environment show that increasing the architectural complexity from a single-layer to a 2-layer 6-sector network results in a remarkable 184% increase in average cell capacity. Furthermore, in the dynamic bandwidth allocation, the inner user-dominated scenario achieves the highest cell capacity, which is 41% higher than that in static bandwidth allocation. At the same time, dynamic allocation also improves fairness in the outer user-dominated scenario, increasing the Jain fairness index by up to 0.444. These results confirm that the combination of the new FFR formulation and adaptive resource allocation significantly improves spectrum efficiency, cell capacity, and fairness, and provides practical guidance for optimizing the implementation of 5G and beyond cellular network deployments.